2021
DOI: 10.1007/s12035-021-02512-9
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine Alleviates Lipopolysaccharide-Induced Hippocampal Neuronal Apoptosis via Inhibiting the p38 MAPK/c-Myc/CLIC4 Signaling Pathway in Rats

Abstract: Dexmedetomidine (DEX) reportedly possessed multiple bioactivities. Here, we mainly investigated the neuroprotective role and detailed molecular mechanism of DEX against lipopolysaccharide (LPS)-induced hippocampal neurons apoptosis. In vivo, Sprague Dawley rats were administered with LPS (10 mg/kg) and/or DEX (30 µg/kg). We found that DEX improved LPS-induced hippocampal microstructure (necrosis and number reduction of neurons in the CA1 and CA3 regions) and ultrastructure (mitochondrial damage) lesions. DEX a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 52 publications
2
6
0
Order By: Relevance
“…In this study, we examined the enriched expressed genes and metabolites of the hippocampus to decipher the possible mechanisms of SAE in the early phase with an LPS-induced experimental sepsis model. The results showed that acute sepsis mice developed inflammation (dramatic upregulation of proinflammatory cytokines), hippocampal neuron injury, and behavior changes, which indicated that a reproducible SAE-like-symptom occurred in hippocampal tissues as in previous findings ( Wang et al, 2013 ; Chen et al, 2021 ).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In this study, we examined the enriched expressed genes and metabolites of the hippocampus to decipher the possible mechanisms of SAE in the early phase with an LPS-induced experimental sepsis model. The results showed that acute sepsis mice developed inflammation (dramatic upregulation of proinflammatory cytokines), hippocampal neuron injury, and behavior changes, which indicated that a reproducible SAE-like-symptom occurred in hippocampal tissues as in previous findings ( Wang et al, 2013 ; Chen et al, 2021 ).…”
Section: Discussionsupporting
confidence: 77%
“…Sepsis initiates a series of systemic inflammatory responses leading to deregulated peripheral inflammation, neuroinflammation, ischemic damage, oxidative stress, and metabolic disorders, disrupting the integrity of the brain–blood barrier (BBB) and, thus, causing the progression of SAE ( Gofton and Young, 2012 ). Furthermore, the histological studies on animal models have shown enlarged ventricles, reduced hippocampus volume, and increased apoptosis of hippocampal neurons in lipopolysaccharide (LPS)-exposure rodents ( Wang et al, 2013 ; Chen et al, 2021 ). Therefore, the hippocampus is an overly sensitive brain region in LPS-triggered animals.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical and animal studies have confirmed associations of decreased hippocampal volume and weight and apoptosis with depression. Hippocampal injury (hippocampal volume reduction and excessive neuronal death) is considered an important marker of the pathogenesis of depression [ 5 , 6 ]. Numerous studies have linked apoptosis to hippocampus damage.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 1 , mice were injected with MPTP 30 mg/kg intraperitoneally for 5 consecutive days to establish a PD subacute model. Dex was injected intraperitoneally 30 minutes before MPTP injection [ 12 , 33 ]. CC (10 μ g/kg) was injected intraperitoneally 30 minutes before Dex.…”
Section: Experimental Materials and Methodsmentioning
confidence: 99%